2020
DOI: 10.1186/s11671-020-03308-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling DNA Translocation Through Solid-state Nanopores

Abstract: Compared with the status of bio-nanopores, there are still several challenges that need to be overcome before solid-state nanopores can be applied in commercial DNA sequencing. Low spatial and low temporal resolution are the two major challenges. Owing to restrictions on nanopore length and the solid-state nanopores' surface properties, there is still room for improving the spatial resolution. Meanwhile, DNA translocation is too fast under an electrical force, which results in the acquisition of few valid data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Multiple approaches have been proposed to slow down the translocation events 20 , which involve either modifying the properties (mostly viscosity) of the electrolyte 10,21,22 , incorporating optical (or magnetic) traps or tweezers 20,23,24 , or using protein tags to slow down the motion of the smaller molecules [25][26][27] . In the last few years, surface charge density modulation has also been suggested to slow down translocation events [28][29][30][31][32][33] , mostly by building nanopores with dielectric materials like Al 2 O 3 29,32,34,35 and HfO 2 30 , or by exploring optoelectronic control of surface charge 33 .…”
mentioning
confidence: 99%
“…Multiple approaches have been proposed to slow down the translocation events 20 , which involve either modifying the properties (mostly viscosity) of the electrolyte 10,21,22 , incorporating optical (or magnetic) traps or tweezers 20,23,24 , or using protein tags to slow down the motion of the smaller molecules [25][26][27] . In the last few years, surface charge density modulation has also been suggested to slow down translocation events [28][29][30][31][32][33] , mostly by building nanopores with dielectric materials like Al 2 O 3 29,32,34,35 and HfO 2 30 , or by exploring optoelectronic control of surface charge 33 .…”
mentioning
confidence: 99%
“…This is a 20-year-old problem for which a wide-ranging solution has remained elusive; most efforts are limited to one type of analyte, usually DNA. Two reviews separated by a decade show that progress is still slow [30,31]. Methods include: magnetic or optical tweezers [32,33], increasing the viscosity of the solution in the e-cell [34], use of an RTIL (room temperature ionic liquid) for the electrolyte [35], binding the protein with SDS (Sodium Dodecyl Sulfate) to allow time for unfolding before the protein enters the pore (and also invest the protein with a higher and uniform electrical charge) [36], threading an analyte string through dual side-by-side nanopores to control its motion [37], and a ring of field effect transistor (FET) gates to control the rate of entry of the analyte into the pore [38].…”
Section: Translocation Speeds In a Nanopore And Methods To Slow Down An Analytementioning
confidence: 99%
“…An effective solution to the first problem will also reduce high frequency noise, which serves to mitigate the third problem. A range of slowdown methods have been reported [10-16]; a recent review can be found in [17]. Except for the solution in [16], which uses an enzyme motor to sequence DNA, a more general solution to the problem remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…There are less restrictions with solid-state nanopores in contrast with biological ones; for example, solid-state nanopores can operate over wider temperature and voltage ranges. Besides, solid-state nanopores are more compatible and even more stable to solvent conditions, and they can be adjusted in diameter with sub-nanometer accuracy (Yuan et al 2020 ). Si3N4 and SiO2 nanopores are among the most broadly employed nanopores, and their manufacturing is in accord with the complementary metal oxide semiconductor industrial integrated circuit processes.…”
Section: Introductionmentioning
confidence: 99%